Characterization of Stormwater Runoff Based on Microbial Source Tracking Methods - Monteiro, Silvia; Queiroz, Gaspar; Ferreira, Filipa; Santos, Ricardo (Frontiers in Microbiology, 2021)
Rainfall and the associated urban runoff have been linked to an increased deterioration of environmental waters, carrying several pollutants including pathogenic microorganisms. Such happens because fecal matter is washed into storm drainage pipes that are afterwards released into environmental waters. Stormwater has not been extensively characterized as it is, because most studies are either performed on drainage pipes that are often impacted by sewage leakage or are performed directly in the environmental waters following a rain event. In this study, stormwater was monitored for the presence of fecal indicator bacteria (FIB) and three potential important sources of fecal contamination in urban environments (human, cats, and dogs) in three distinct basins in Portugal. Stormwater was collected in sterilized plastic boxes inserted in the storm drains, collecting only runoff. High concentration of fecal indicator bacteria was detected in most of the samples analyzed and a high percentage of the samples displayed at least one source of fecal contamination with strong relationship between the number of detected sources and the precipitation levels. Although there was no statistical correlation between the locations and FIB or the presence of source markers, the results provide a geographical information on the type of urban use in each basin. To the best of our knowledge, this is the first study analyzing the runoff collected directly from the streets. This study suggests that, in urban areas, stormwater runoff is highly impacted by fecal matter before any cross-contamination in the drainage system and may pose a high risk to human health and to the environment, particularly if reuse of this water is to be done without any further treatment.